2013
DOI: 10.1038/onc.2012.605
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of RNF2 induces apoptosis by regulating MDM2 and p53 stability

Abstract: RNF2, also known as Ring1B/Ring2, is a component of the polycomb repression complex 1 (PRC1). RNF2 is highly expressed in many tumors, suggesting that it might have an oncogenic function, but the mechanism is unknown. Here we show that knockdown of RNF2 significantly inhibits both cell proliferation and colony formation in soft agar, and induces apoptosis in cancer cells. Knockdown of RNF2 in HCT116 p53+/+ cells resulted in significantly more apoptosis than was observed in RNF2 knockdown HCT116 p53−/− cells, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 29 publications
1
45
0
Order By: Relevance
“…Contrastingly, another polycomb complex protein RNF2, also known as Ring1B/Ring2 is seen to bind with both p53 and MDM2 in colon cancer cell lines and promote MDM2-mediated p53 ubiquitination. RNF2 overexpression also increases the half-life of MDM2 and inhibits its ubiquitination[118],[119]. These observations indicate that polycomb proteins play important roles in p53/MDM2 regulation and may present novel targets for cancer therapy or prevention.…”
Section: Modulators Of the Mdm2-p53 Pathwaymentioning
confidence: 79%
“…Contrastingly, another polycomb complex protein RNF2, also known as Ring1B/Ring2 is seen to bind with both p53 and MDM2 in colon cancer cell lines and promote MDM2-mediated p53 ubiquitination. RNF2 overexpression also increases the half-life of MDM2 and inhibits its ubiquitination[118],[119]. These observations indicate that polycomb proteins play important roles in p53/MDM2 regulation and may present novel targets for cancer therapy or prevention.…”
Section: Modulators Of the Mdm2-p53 Pathwaymentioning
confidence: 79%
“…The MDM2-p53-negative feedback controls p53 signaling at proper range with respect to cell stress [10], [11]. Besides a few direct E3 ligases targeting p53, more and more E3 ligases are found to modulate MDM2-p53 complex, such as RNF31 and RNF2 [12], [13].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has shown that the knockdown of Rnf2 significantly inhibits cell proliferation and colony formation in the colon cancer HCT116 cell line (31). In addition, it was also associated with induction of apoptosis by regulating MDM2 and p53 stability (31). Similarly, Su et al (9) reported that Rnf2 is essential for the proliferation of ovarian and testicular cancer cells by functioning as an E3 ligase for p53 degradation.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that the knockdown of Rnf2 significantly inhibits cell proliferation and colony formation in the colon cancer HCT116 cell line (31). In addition, it was also associated with induction of apoptosis by regulating MDM2 and p53 stability (31).…”
Section: Discussionmentioning
confidence: 99%